Ranula: A Rare Cause of Airway Obstruction. Issue 5 (September 2016) - Ahuja, Neha K.; Tandon, Rajive
Abstract : Ranulas are mucus-filled cysts that originate from the extravasation of mucus from the sublingual gland. They are typically painless, slow-growing swellings on the floor of the mouth associated with trauma or excretory ductal obstruction. They can, however, form rapidly, leading to airway compromise and respiratory failure. We present a case of a 34-year-old man requiring intensive care unit admission for closer airway monitoring due to rapid progression of a simple ranula. Airway obstruction resolved promptly with steroids and antibiotics.